PENGGUNAAN MODEL PEMBELAJARAN KOPERATIF TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Tri Wenti Amelina (Departemen Matematika, 2018)
The understandingof mathematical concept has an important role in the purpose of learning so that later learners will be able to understand the objectives of other mathematics learning. However, in reality from the learning results, it can be seen that the students understanding is still low, so it needs to be improved, in order to understand the concept well. The purpose of this study is to describe whether the understanding of the mathematical concepts of learners who learn withThink Talk Write cooperative learning model is better than understanding the mathematical concepts of learners who learn with conventional learning. Based on the results of data analysis, at the level of real α = 0.05 , it can be concluded that the understanding of the mathematical concepts of learners who learn withThink Talk Write cooperative learning model better than understanding mathematical concepts of students who learn with conventional learning.Keywords - Understanding Mathematical Concept, Cooperative Learning Model of Think Talk Write Type, Conventional Learning